2021
DOI: 10.3390/ijms222212400
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of CP190 Interaction with Architectural Proteins in Drosophila Melanogaster

Abstract: Most of the known Drosophila architectural proteins interact with an important cofactor, CP190, that contains three domains (BTB, M, and D) that are involved in protein–protein interactions. The highly conserved N-terminal CP190 BTB domain forms a stable homodimer that interacts with unstructured regions in the three best-characterized architectural proteins: dCTCF, Su(Hw), and Pita. Here, we identified two new CP190 partners, CG4730 and CG31365, that interact with the BTB domain. The CP190 BTB resembles the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 71 publications
4
25
0
Order By: Relevance
“…Among these, we find proteins such as Boundary Element-Associated Factor of 32kDa (BEAF-32), Chromator (Chro), Putzig (Pzg), and Centrosomal protein 190kDa (Cp190) that function in regulating genomic architecture, suggesting a unstudied role for KDM5 in this process. (64)(65)(66)(67)(68)(69) In addition, we identified proteins critical for forming the transcriptional pre-initiation complex (TPIC), which is consistent with the promoter-proximal binding of KDM5 proteins across species. (25,44,(70)(71)(72) Using a recent cryo-EM structure of the human TPIC, we found that distinct surfaces interacted with KDM5, consistent with the specificity of biotinylation using TurboID-KDM5.…”
Section: Proximity Labeling Identifies New Potential Kdm5 Interacting...supporting
confidence: 63%
See 1 more Smart Citation
“…Among these, we find proteins such as Boundary Element-Associated Factor of 32kDa (BEAF-32), Chromator (Chro), Putzig (Pzg), and Centrosomal protein 190kDa (Cp190) that function in regulating genomic architecture, suggesting a unstudied role for KDM5 in this process. (64)(65)(66)(67)(68)(69) In addition, we identified proteins critical for forming the transcriptional pre-initiation complex (TPIC), which is consistent with the promoter-proximal binding of KDM5 proteins across species. (25,44,(70)(71)(72) Using a recent cryo-EM structure of the human TPIC, we found that distinct surfaces interacted with KDM5, consistent with the specificity of biotinylation using TurboID-KDM5.…”
Section: Proximity Labeling Identifies New Potential Kdm5 Interacting...supporting
confidence: 63%
“…Among these, we find proteins such as BEAF-32, Chromator (Chro), Putzig (Pzg), and Cp190 that function in regulating genomic architecture, suggesting a unstudied role for KDM5 in this process. [66][67][68][69][70][71] To confirm our MS data, we performed western blots on input and streptavidin pulldowns and probed with antibodies specific for BEAF-32 and CP190. This confirmed enrichment of these two proteins in both NT-KDM5 and CT-KDM5 compared to dCas9:TurboID-expressing and control flies (Fig.…”
Section: Proximity Labeling Identifies New Potential Kdm5 Interacting...mentioning
confidence: 92%
“…[62] The same mechanism was proposed for the interaction between the BTB of the Drosophila CP190 protein and unfolded peptides from architectural proteins. [63] Most of these peptides contain two short conserved hydrophobic regions that bind to the hydrophobic groove of the CP190 BTB domain according to mutagenesis data. [63] 2.…”
Section: Multimerization Of Btb Domainsmentioning
confidence: 99%
“…[63] Most of these peptides contain two short conserved hydrophobic regions that bind to the hydrophobic groove of the CP190 BTB domain according to mutagenesis data. [63] 2. Miz1-HUWE-1 interaction.…”
Section: Multimerization Of Btb Domainsmentioning
confidence: 99%
“…The most well-studied of these, CP190, has four C2H2 zinc finger domains that appear to be involved in protein-protein interactions rather than DNA binding [29, 30]. The N-terminal BTB/POZ domain of CP190 forms stable homodimers [21, 29, 31-33]. CP190 is required for the activity of housekeeping promoters and insulators [34-38].…”
Section: Introductionmentioning
confidence: 99%